Parents’ Extent In and Challenges to Academic Support to Their Children in Kenyan Public Primary Schools in Nandi Central Sub- County - Achoka, J.S.K; Chepsiror, E.; Odoyo, F.S.; Chepchirchir, G. (Advances in Social Sciences Research Journal, 2015)
The KCPE results released in Nandi Central Sub-County showed that the bottom 64 out of 186 schools which attained below the average mark 250 out of 500 marks were all public primary schools (MOEST, 2013) hence the study sought to investigate influence of parents’ academic support on performance of class eight pupils in public primary schools in Nandi Central Sub- County, Kenya. The study was guided by these research questions: What is the role of parents in enhancing the performance of class eight pupils in public primary schools in Nandi Central Sub-County Kenya?, What is the perception of head teachers, teachers, pupils and parents concerning parents’ support to class eight pupils in public primary schools in Nandi Central Sub-County Kenya? What challenges hinder the academic support of parents in public primary schools in Nandi Central Sub-County Kenya? How does parents’ academic support influence performance of class eight pupils in public primary schools in Nandi Central Sub- County, Kenya? And how can the parents of class eight pupils get actively involved in improving the academic performance in public primary schools in Nandi Central Sub-County, Kenya? This study will be significant to the MOEST, head teachers, teachers, parents and SMC. Epstein, (2002) theoretical model on six- type’s parents’ involvement was used to guide the study Cross-section descriptive Survey design was used in the study. The target population consisted of all public primary schools in Nandi Central Sub-County, Kenya which consist of N=186 giving a total target population of N=11,032 and a sample size of n=390. Stratified sampling was used to stratify Sub-County schools in to 10 zones and the schools in to 8 class strata and class eight strata was chosen for the study. Simple random technique was used to sample: 3 schools in every zone, double streams and class eight pupils. The head teachers, class teachers and the parents of selected pupils were included. Qualitative data collection instruments were used to facilitate triangulation with those from quantitative data collection instruments then analyzed using descriptive statistics. 2 schools were used for pilot for the purpose of pre-testing instruments for data collection and to ensure their reliability. The data was analyzed using frequencies, percentages and mean and summarized in tables and triangulated with qualitative data thereby drawing conclusion. The findings of the study indicate that parents’ support influence class eight academic performance. Recommendations include: the government should establish a policy that stipulates how parents should play a central role in their children’s education so as to contribute to a child’s academic performance, the government should increase the subsidy per pupil to enable schools to buy enough teaching learning materials among others. The study made suggestions for further research.